ISOLASI DAN IDENTIFIKASI BAKTERI POTENSIAL PATOGEN PADA IKAN NILA (Oreochromis niloticus) DI KOLAM BUDIDAYA PATUMBAK Isolation and Identification of Potential Pathogenic Bacteria in Tilapia (Oreochromis niloticus) in Patumbak Pond Aquaculture - Ruth Aprilyanti Napitupulu; Dwi Suryanto; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Tilapia culture is highly affected by fish diseases, which may be occured because of change in environment. This study was aimed to know potential pathogenic bacteria in nila fish (Oreochromis niloticus). Screening and isolation of the bacteria were done in Balai Karantina Ikan, Pengendalian Mutu dan Keamanan Hasil Perikanan Kelas I Medan I. Identification of the bacteria was conducted using Vitek 2 Compact in RS Murni Teguh. Five potential pathogenic bacteria were found to infect nila fish i.e. Kocuria kristinae and Stenotrophomonas maltophilia of brain, Aeromonas hydrophila of liver, Staphylococcus lentus of kidney and Staphylococcus warneri of skin sample. Water temperature was 32 oC with pH of 6,9 and DO of 2,96 mg/lKeywords : Patumbak, Potential Pathogenic Bacteria, Tilapia, Water Quality.